Lip Augmentation with Autografts and Allografts - Mella, Jeffrey; Beck, Jenna Van; Hilger, Peter (Facial Plastic Surgery, 2025)
Lip augmentation is a popular cosmetic procedure aimed at enhancing lip volume, symmetry, and contour, which significantly influences overall facial aesthetics.Historically, lip enhancement dates back centuries, with various cultures emphasizing the allure of fuller lips. Lip Augmentation with alloplastic implants like silicone and Gore-Tex was favored for a time for their versatility and consistency, but modern practice has increasingly favored biologically derived implants due to their natural integration, reduced complications, and desirable texture. Autologous tissues, such as superficial muscular aponeurotic system grafts, offer additional benefits including minimal immune response, high compatibility, and lasting enhancement.The technique is consistent across most implants which includes making vertical stab incisions just medial to the oral commissure, dissecting in an intramuscular plane within the orbicularis marginalis just under the white roll, and then tunneling the implant to the other side with a tendon passer. The lips are stretched to incorporate the implant and inspected for irregularities prior to closing the incisions.Augmentation with implants offers the appeal of a more permanent augmentation minimizing the need for repeated interventions. Successful lip augmentation enhances lip volume and contour while preserving facial aesthetic harmony and respecting the dynamic anatomical function of the lips.
Keywords: allograft; autograft; implant; lip; augmentation